Accurate 3D Characterization of Catalytic Bodies Surface by Scanning Electron Microscopy. Issue 14 (12th June 2019) - Gontard, Lionel C.; Cauqui, Miguel Ángel; Yeste, María Pilar; Ozkaya, Dogan; Calvino, José Juan
Abstract: Catalytic bodies of millimetric dimensions are frequently used in industrial catalysis. The engineering process applied on the raw nanocatalyst during the fabrication and the working conditions affect the spatial and chemical relations of the exposed surface of the catalytic device. Hence, for improving their synthesis and for monitoring the evolution during its life cycle it is important understanding the actual heterogeneities of their surfaces. In this work scanning electron microscopy, photogrammetry and X‐Ray spectroscopy are combined to perform physico‐chemical characterization in three‐dimensions and with high resolution of the surface of commercial water gas shift catalyst bodies. By analyzing a phase of carbon present on their surface we show that the method provides measurements that are at the same time reliable, accurate and precise. Abstract : Beyond the conventional : Conventional 2D scanning electron microscopy provides limited information when used for measuring the surfaces of three‐dimensional catalytic devices or catalytic particles. Here we describe a methodology called 3DSEM‐EDXS for the accurate physico‐chemical characterization of catalytic surfaces in three‐dimensions, with high resolution. The technique can be applied without modification of existing equipment.